2017
DOI: 10.14202/vetworld.2017.888-894
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol concentration, pain and sedation scale in free roaming dogs treated with carprofen after ovariohysterectomy

Abstract: Background and Aim:One of the topic issues in animal welfare activities is the free roaming dog welfare especially in developing countries such as Serbia. The way of controlling population of free roaming dogs is their reproduction with the method of “Catch-Neuter-Release.” This complex process consists of capturing free roaming dogs in public areas, sterilizing, and returning them to the public area from which they were temporarily removed. Ovariohysterectomy present the period with a high intensity of stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…For instance, it has been suggested that meloxicam may control acute postoperative pain for up to 20 hours after a laparotomy, with greater efficacy than that of butorphanol [53]. Carprofen has been widely demonstrated in studies of the perioperative period in dogs [39,48,54] to provide satisfactory analgesia for up to 18 hours post-surgery. Furthermore, premedication, as opposed to postoperative administration, of carprofen provides superior analgesia [12,55].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been suggested that meloxicam may control acute postoperative pain for up to 20 hours after a laparotomy, with greater efficacy than that of butorphanol [53]. Carprofen has been widely demonstrated in studies of the perioperative period in dogs [39,48,54] to provide satisfactory analgesia for up to 18 hours post-surgery. Furthermore, premedication, as opposed to postoperative administration, of carprofen provides superior analgesia [12,55].…”
Section: Discussionmentioning
confidence: 99%
“…Ovariohysterectomy (OVH), gastrotomy (GST), and intestinal resection and anastomosis (IRA) are surgical procedures that are commonly performed in practice. They are performed on the elective and emergency basis and are capable of eliciting variable degrees of surgical stress response which if not allayed by the use of anesthetics and analgesics can result in untoward effects [ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some methods are assessing the short-term variations, while others are focusing on the long-term changes. For the chronic pain assessment, it would be clinically more useful to be able to determine the long-term variations of cortisol, but measuring this parameter could be misleading since multiple cut-off values were shown in the literature, depending on the method used, and many clashing opinions on this subject emerged in the last decade [4,7,21,24].…”
Section: Discussionmentioning
confidence: 99%
“…An Objective pain measurement method would be gait analysis. The combination of various methods should be taken into consideration [7,8,24,25,34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation